Host plant‐related genomic differentiation in the European cherry fruit fly, Rhagoletis cerasi. Issue 20 (13th October 2019) - Bakovic, Vid; Schuler, Hannes; Schebeck, Martin; Feder, Jeffrey L.; Stauffer, Christian; Ragland, Gregory J.
Abstract: Elucidating the mechanisms and conditions facilitating the formation of biodiversity are central topics in evolutionary biology. A growing number of studies imply that divergent ecological selection may often play a critical role in speciation by counteracting the homogenising effects of gene flow. Several examples involve phytophagous insects, where divergent selection pressures associated with host plant shifts may generate reproductive isolation, promoting speciation. Here, we use ddRADseq to assess the population structure and to test for host‐related genomic differentiation in the European cherry fruit fly, Rhagoletis cerasi (L., 1758) (Diptera: Tephritidae). This tephritid is distributed throughout Europe and western Asia, and has adapted to two different genera of host plants, Prunus spp. (cherries) and Lonicera spp. (honeysuckle). Our data imply that geographic distance and geomorphic barriers serve as the primary factors shaping genetic population structure across the species range. Locally, however, flies genetically cluster according to host plant, with consistent allele frequency differences displayed by a subset of loci between Prunus and Lonicera flies across four sites surveyed in Germany and Norway. These 17 loci display significantly higher FST values between host plants than others. They also showed high levels of linkage disequilibrium within and between Prunus and Lonicera flies, supporting host‐related selection and reduced gene flow. Our findings support the existence of sympatric host races in R. cerasi embedded within broader patterns of geographic variation in the fly, similar to the related apple maggot, Rhagoletis pomonella, in North America.